Julian of Norwich and the Sin of Forgetfulness - Tracy, Kisha G. (Journal of medieval religious cultures, 2015)
This essay considers how memory is pervasive in Julian of Norwich's Revelations and why recollection and forgetfulness are essential to her experiences even from the beginning of the short version. She defines a certain type of forgetfulness, that which causes a separation between her and God, as sinful, and this perception of sin influences the analysis and composition of her visions. By recollecting in specific ways, she attempts to provide a remedy for her sin of forgetfulness.